371. Cluster of carbapenemase-producing Enterobacterales secondary infections during the COVID-19 crisis at a New York City hospital. (31st December 2020) - Gomez-Simmonds, Angela; Annavajhala, Medini K; McConville, Thomas H; Dietz, Donald E; Shoucri, Sherif M; Laracy, Justin C; Nelson, Brian; Whittier, Susan; Uhlemann, Anne-Catrin; Uhlemann, Anne-Catrin
Abstract: Background: Patients with COVID-19 may be at increased risk for secondary bacterial infections. At our quaternary care hospital in New York City, the rapid escalation of COVID-19 cases was accompanied by a massive surge in the need for hospital and critical care capacity. During this time, we noted a increase in infections caused by carbapenemase-producing Enterobacterales (CPE). Methods: We retrospectively assessed microbiology data to identify patients with positive testing for SARS-CoV-2 who had clinical cultures with meropenem-resistant and/or carbapenemase gene-positive Enterobacterales. We obtained microbiological and clinical data by manual chart review. Available clinical isolates underwent long-range genomic sequencing using the MinION (Oxford) for rapid genotyping, resistance gene detection, and phylogenetic analysis. Results: From March 1 to May 18, we identified 33 CPE isolates from 13 patients, including 29 Klebsiella pneumonia and four Enterobacter cloacae . Most patients (11/13) had a positive respiratory culture, and 7/13 developed bacteremia. All patients had prolonged, complex hospitalizations with extensive antibiotic exposure. We performed long-range sequencing on 19 isolates from 12 patients. 15/16 K. pneumoniae isolates belonged to sequence type (ST) 258 encoding KPC (14 KPC-2; 1 KPC-3); one ST70 isolate encoded KPC-2. All four E. cloacae isolates belonged to ST270 and encoded NDM-1. Phylogenetic analysis of ST258 isolates including historical isolates from our hospital revealed a distinct lineage of isolates from COVID-19 patients (72% bootstrap support), with expected clustering of isolates from the same patient and patients that were cohorted together. Conclusion: While CPE have declined substantially in New York City in recent years, increased detection in patients with COVID-19 may signal a reemergence of these highly resistant pathogens in the wake of the global pandemic. System-level factors, such as the rapid scale-up of critical care capacity, while clearly needed to address the unprecedented reach of COVID-19, may have contributed to isolate clustering in these patients. Increased surveillance and antimicrobial stewardship efforts will be needed to mitigate the impact of CPE in the future. Disclosures: All Authors : No reported disclosures